Public Goods and Minimum Provision Levels: Does the Institutional Formation Affect Cooperation?. (10th April 2019) - Martinsson, Peter; Persson, Emil
Abstract: We investigate experimentally the role of institutional formation on the implementation of a binding minimum contribution level to a public good. Groups either face the minimum level exogenously imposed by a central authority, or are allowed to decide for themselves by means of a group vote whether a minimum level should be implemented. We find that a binding minimum contribution level has a positive and substantially significant effect on cooperation. Interestingly, we do not find an additional positive effect of democracy in the context of our experiment; the minimum‐level intervention is as effective when exogenously implemented as when endogenously chosen.